PERUBAHAN BAHASA DI LINGKUNGAN KECAMATAN CIBARUSAH - Novita Puspahaty (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2017)
This research aimed to answer these research questions: (1) Do all social stratum of Desa Sindang Mulya, Kecamatan Cibarusah undergo a language change? (2) What kinds of things influence the language change? To obtain the findings, this research applied a qualitative method in which the findings were analysed descriptively. The findings show that everyone living in Desa Sindang Mulya, Kecamatan Cibarusah experienced the language shifting from using Sundanese Language as their local language to Bahasa Indonesia as the national language. In addition, the findings indicated that the language change seemed to be a threat for Sundanese language in Desa Sindang Mulya, Kecamatan Cibarusah.